2007
DOI: 10.1111/j.1365-2125.2007.02942.x
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac and acute myocardial infarction in patients with no major risk factors

Abstract: What is already known about this subject • We recently published the results of a study on the risk of acute myocardial infarction (AMI) AimsTo explore further a recent finding that long-term users of diclofenac are at increased risk of acute myocardial infarction (AMI) similar to users of rofecoxib and celecoxib. MethodsUsing the General Practice Research Database, we conducted three separate nested case-control studies of three nonsteroidal anti-inflammatory drugs (NSAIDs) where use started after 1 Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
3
14
0
1
Order By: Relevance
“…Despite the use of the same database, the results cannot directly be compared because of varying definitions of the exposure timewindows, different time-periods included and matching variables. Taking this into account, the overall results of the present cohort study were broadly similar to most of the previously published GPRD studies [30][31][32][33][34][35][36]. A recent GPRD case-control study concluded that long-term use of diclofenac was associated with substantially increased risks of MI, whilst this conclusion did not apply to ibuprofen or naproxen [35].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite the use of the same database, the results cannot directly be compared because of varying definitions of the exposure timewindows, different time-periods included and matching variables. Taking this into account, the overall results of the present cohort study were broadly similar to most of the previously published GPRD studies [30][31][32][33][34][35][36]. A recent GPRD case-control study concluded that long-term use of diclofenac was associated with substantially increased risks of MI, whilst this conclusion did not apply to ibuprofen or naproxen [35].…”
Section: Discussionsupporting
confidence: 87%
“…General Practice Research Database has been used in several other studies to study the risk of MI in patients using traditional NSAIDs [30][31][32][33][34][35][36] or selective Cox-2 inhibitors [37]. Despite the use of the same database, the results cannot directly be compared because of varying definitions of the exposure timewindows, different time-periods included and matching variables.…”
Section: Discussionmentioning
confidence: 99%
“…They also discovered a cumulating risk for MI with diclofenac up to 2.03 at >300mg compared to 1.13 at <150 mg. Jick et al further specified the dependence of an escalation of relative risk with the number of prescriptions of tNSAID (diclofenac, ibuprofen and naproxen) and found only for diclofenac an increase up to a RR of 2. [40]. The study by GarciaRodriguez confirms these results as it found that the risk increased with current NSAID intake, treatment duration and daily dose [42].…”
Section: Clinical Data For An Association Of Diclofenac With Atherothsupporting
confidence: 83%
“…Jick et al analyzed in a nested case control study cases of AMI associated with diclofenac, ibuprofen or naproxen intake in patients with no major risk factors and found an adjusted risk ratio for diclofenac of 1.30 vs. 1.10 in naproxen or ibuprofen users. Diclofenac showed an increasing risk ratio up to 2 with increasing numbers of prescriptions [40]. Similar results were obtained by van Staa et al, who scanned the General Practice Research Database like Jick et al In this analysis, the relative risk for AMI increased with numbers of prescriptions and raising dosages, resulting in a cumulative risk of 1.21 for diclofenac and 1.04 and 1.03 for ibuprofen and naproxen respectively [41].…”
Section: Clinical Data For An Association Of Diclofenac With Atherothsupporting
confidence: 75%
“…A positive dose-response relationship has been demonstrated for both diclofenac and ibuprofen and risk of coronary artery disease. [37][38][39][40] Whether or not an increased risk of ischemic stroke exists at higher doses for these or other NSAIDs requires further investigation.…”
Section: Discussionmentioning
confidence: 99%